Design, Implementation, and Testing of a Small Bidirectional Locking Clutch for Hand Prostheses. Issue 1 (January 2015) - Vaidya, Narendra; Buchholz, Bryan
<x xml:space="preserve">Abstract</x> ABSTRACT Introduction: This study presents the design, implementation, and testing of a miniature bidirectional locking clutch. This is a sprag-style design that locks in either direction of rotation. In a case when the load in the hand tries to back drive the digits, this clutch allows the hand to hold its position once the control signal or power is removed. This also helps to conserve power supplied by the battery pack to the prosthesis, making the battery last longer. The size of this clutch is 22.5 mm in width and height, and 9.26 mm thick excluding the length of input and output shafts that extend out. Materials and Methods: The clutch was tested using a manual load on the input and output side of the clutch to verify the design concept and functionality. Results and Conclusions: Although functional, the clutch had dimensional stackup tolerance issues; the clutch functioned perfectly up to input torque of 0.3 N m when driven directly by a DC motor.